EFFECT OF BODY WEIGHT AND SCROTAL CIRCUMFERENCE ON SEMEN PRODUCTION TRAITS IN CROSSBRED HOLSTEIN FRIESIAN BULLS - GOPINATHAN, A; SIVASELVAM, S N; KARTHICKEYAN, S M K; KULASEKAR, K (The Indian Journal of Animal Reproduction, 2022)
The present study aimed to investigate the influence of body weight and scrotal circumference and its phenotypic correlation with semen production traits in crossbred Holstein Friesian bulls. Overall least-squares mean for semen volume, sperm concentration, mass activity, initial sperm motility, post-thaw motility and number of doses/ejaculate were 4.10±0.06 ml, 842.7±21.7 million/ml, 2.11±0.03, 55.6±0.0%, 49.8±0.0% and 196.92±5.4, respectively. The body weight and scrotal circumference of crossbred bulls influenced (p<0.01) all semen production traits. The body weight was positively correlated (p<0.01) with scrotal circumference (0.85), semen volume (0.56), sperm concentration (0.12), mass activity (0.41) and number of doses/ejaculate (0.49). The phenotypic correlations of scrotal circumference with semen volume (0.47), sperm concentration (0.06), mass activity (0.39) and number of doses/ejaculate (0.36) were positive (p<0.05). In brief, the bulls having body weight between 450 to >650 kg and scrotal circumference >36 cm exhibited better performance with regard to majority of the semen production traits.